Imported Oil and U.S. National Security - Crane, Keith (RAND Corporation, 2009)
In 2007, the United States imported 58 percent of the oil it consumed. This book critically evaluates commonly suggested links between these imports and U.S. national security and assesses the economic, political, and military costs and benefits of potential policies to alleviate imported oil?related challenges to U.S. national security.